Brave Harriet : the first woman to fly the English Channel - Moss, Marissa; Payne, C. F. (San Diego : Silver Whistle, 2001)
The first American woman to have received a pilot's license describes her April 1912 solo flight across the English Channel, the first such flight by any woman.
Wilson's Children, October 2010.
School Library Journal, September 2001.
Book Links (A.L.A.), February 2002.
Booklist starred, July 2001.
Publisher's Weekly, July 2001.
Bulletin (Center for Children's books), January 2002.
Keywords: Quimby, Harriet, -- 1875-1912 -- Juvenile literature; Quimby, Harriet, -- 1875-1912.; Quimby, Harriet, -- 1875-1912.; Women air pilots -- United States -- Biography -- Juvenile literature; Aeronautics -- Flights; Women -- Biography; Air pilots; Aeronautics; Women air pilots -- United States -- Biography; Aeronautics; Women -- Biography; Air pilots; Women air pilots -- Biography; Aeronautics; Women -- Biography; English Channel; Nonfiction picture books